PENERAPAN PENDEKATAN PEMBELAJARAN KONSTRUKTIVISME DENGAN BANTUAN LKS PADA PEMBELAJARAN FISIKA DI SMKN 1 LINTAU BUO - Komala, Ratih Aresta; Lizelwati, Novia; Asmendri, Asmendri (Jurnal Pembelajaran MIPA, 2014)
The purpose of this research is to know the result of student physics at applying of constructivism the study approach with LKS. The type of this research is guasi experiment with research device in the form of Posttest only control group design. Research procedur differentiated into three phase that is preparation, execution and solution. Analyze technique of data is used normalitas test, homogeneity test and hypothesis test. The Result of research, the first of result at affective aspect andÂ psychomotor experience improvement at each meet. Average value the result of student physics in experiment class is 79.703 while average value in control class is 70.465. The Result of research also shows raised hypothesis at this research is accepted, so that it can be concluded, the result of student in experiment class which applying of constructivism the study approach with LKS is better than of control classes.Key Words: constructivism approach, LKS, Physics Study